The Photodynamic Effect of Different Size ZnO Nanoparticles on Cancer Cell Proliferation In Vitro - Chen Baoan; Li Jingyuan; Guo Dadong; Wang Xuemei; Wang Huangping; Jiang Hui (Nanoscale Research Letters, 2010)
Abstract Nanomaterials have widely been used in the field of biological and biomedicine, such as tissue imaging, diagnosis and cancer therapy. In this study, we explored the cytotoxicity and photodynamic effect of different-sized ZnO nanoparticles to target cells. Our observations demonstrated that ZnO nanoparticles exerted dose-dependent and time-dependent cytotoxicity for cancer cells like hepatocellular carcinoma SMMC-7721 cells in vitro. Meanwhile, it was observed that UV irradiation could enhance the suppression ability of ZnO nanoparticles on cancer cells proliferation, and these effects were in the size-dependent manner. Furthermore, when ZnO nanoparticles combined with daunorubicin, the related cytotoxicity of anticancer agents on cancer cells was evidently enhanced, suggesting that ZnO nanoparticles could play an important role in drug delivery. This may offer the possibility of the great potential and promising applications of the ZnO nanoparticles in clinical and biomedical areas like photodynamic cancer therapy and others.